Seven school-related disasters: Lessons for policymakers and school personnel - Laura M. Stough; Donghyun Kang; Sungyoon Lee (Arizona State University, 2018)
Students are highly dependent on the emergency planning and evacuation decisions made by policymakers and school personnel when disasters occur. The purpose of this study was to examine selected cases of school-related disasters, highlighting how factors of the school context intersected with natural hazards and subsequently affected schoolchildren. Purposeful maximal sampling was used to select school-related disaster cases for their geographical diversity, different instructional contexts, and types of initiating hazards. Among these, seven cases with broad considerations pertaining to educational policy and safe school environments were selected. A within-case analysis was conducted of each case, followed by a cross-case thematic analysis. Six overarching factors were found in the thematic synthesis of the findings. First, school safety practices apply anytime children are under the supervision of school personnel, making knowledge of emergency procedures across multiple types of school settings essential. Second, elements that place schoolchildren at risk also place school personnel at risk. Third, teachers and school administrators need to be well-trained and knowledgeable enough to make independent decisions in emergency situations. Fourth, children must know emergency procedures so they may take independent action, given teachers are also at-risk during disasters. Fifth, most school disasters can be prevented through safe school construction. Finally, it is the responsibility of policymakers to ensure schools are safe learning environments for children. By participating in and advocating for a culture of preparedness, educational policymakers can better protect schoolchildren, as well as school personnel, in disaster situations.